Análise de atividades didáticas com vistas à promoção de letramento científico - Arnt, Janete Teresinha (2012)
This study proposes a critical analysis of activities (extracted) from textbooks of English for Academic Purposes in order to investigate the textbook s practices of promotion of scientific literacy. The focus of analysis is to examine how the textbooks appropriate knowledge produced by research on language, reading as critical literacy, scientific literacy and on the genres they explore (in the case of this research, studies on the science popularization news genre). From the analysis of the reading approaches and the concept of language that underlies the didactic activities, I intend to investigate the extent the activities that constitute this material promote the insertion of students in scientific practices. The corpus is constituted of two units, one of a textbook frequently used to teach English for Academic Purposes in the degrees of Computing Science, Statistics, Geography and Languages at the Federal University of Santa Maria and the other used in extension courses at Federal University of Santa Catarina. Besides being used in these courses, the textbooks were selected because most of their activities are formulated from the genre science popularization news. In these units, first the exercises were classified into prereading, reading and post-reading activities so as to investigate the approach of language that underpin their practices. After that, we investigated the extent to which activities on language proposed in these materials corroborate the concept of language as genre. Finally, we analyze to what extent these activities aimed at promoting scientific literacy. Besides that, we also present a reelaboration of the activities that intends to promote scientific literacy by exploring the genre science popularization news in its ideational, interpersonal, and textual metafunctions. Thus, this study aims at offering possibilities of utilization of the genre science popularization news for promoting scientific literacy and subsidizing the construction of didactic material for English for Academic Purposes.